Gelehrte Theologie und gelebte Religion - Vögele, Wolfgang (Pastoraltheologie, 2003)
The author discusses recent concepts of systematic theologians on the purpose of university theology. He suggests that also systematic theology takes everyday-life religion as shown in empirical research into consideration, and by its interpretation improves theological competence.
Aufsatz
Keywords: Theologiestudium; Religiosität; Theologie